Laboratory studies on CO2 foam flooding enhanced by a novel amphiphilic ter-polymer - Xu, X.; Saeedi, Ali; Liu, K. (2016)
Previous research has demonstrated Hydrolyzed Poly-Acrylamide (HPAM) exhibits poor thickening ability even under mild reservoir condition; furthermore, it would detrimentally affect the foamability of the foaming system. This work presents the finding of an investigation using a novel polymer named AVS which is a ter-polymer of AM, AMPS and one functional monomer and which can stabilize CO2 foam under relatively high salinity and temperature without greatly compromising foamability. Core flooding experiments indicate the optimal injection method for AVS enhanced CO2 foam flooding is direct injection of foam and the suitable gas/liquid ratio is determined to be around 3:1. Under these experimental conditions, tertiary oil recovery differences between foam flooding enhanced by AVS and that enhanced by HPAM are 3.7% and 6.6% for low and high permeability respectively, suggesting AVS possesses great EOR potential in the CO2 foam flooding process.